2009
DOI: 10.1088/0022-3727/42/21/215006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic studies of Fe-doped martensitic Ni2Mn1.44Sn0.56-type Heusler alloy

Abstract: Localization and magnetism of Fe replacing either Mn or Ni in the Ni2Mn1.44Sn0.56-type Heusler alloy have been systematically investigated using magnetization, scanning electron microscopy and Mössbauer spectroscopy. It has been shown that the addition of Fe either in Mn or in Ni sites reduces the fraction of the Mn-rich NiMnSn-type Heusler alloys that has short-range antiferromagnetic interactions; consequently it reduces the martensitic–austenitic transition temperature and increases the thermal hysteresis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
4
15
0
Order By: Relevance
“…A Shimadzu SSX 550 scanning electron microscope (SEM) was used to confirm the phase formation and its composition, using the energy dispersive X-ray spectroscopy (EDX), from polished flat pieces obtained from the central part of the annealed pellets. As we previously reported for other set of samples similarly prepared [20,21], more than 99% of the SEM image areas can be associated with a single phase corresponding to the L21-B2-type structure in accord with the X-ray diffraction result. These EDX results confirm that the nominal compositions indeed correspond to the planned alloys.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…A Shimadzu SSX 550 scanning electron microscope (SEM) was used to confirm the phase formation and its composition, using the energy dispersive X-ray spectroscopy (EDX), from polished flat pieces obtained from the central part of the annealed pellets. As we previously reported for other set of samples similarly prepared [20,21], more than 99% of the SEM image areas can be associated with a single phase corresponding to the L21-B2-type structure in accord with the X-ray diffraction result. These EDX results confirm that the nominal compositions indeed correspond to the planned alloys.…”
Section: Methodssupporting
confidence: 88%
“…Field cooled (FC) and field heated (FH) magnetization versus temperature [M(T)] curves were recorded between 70 and 320 K using a commercial physical property measurement system (Quantum Design PPMS) coupled to an Evercool model cryostat and under an applied DC magnetic field up to 50 kOe. These curves were obtained using protocols described elsewhere [21]. As previously reported, any thermal hysteresis observed between FC and FH M(T) curves can directly be associated with the first-order character of the martensitic phase transition (MPT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the crystal structure of these compounds strongly depends on the composition and the quenching rate, which can produce site disorder and will drastically influence the magnetic properties due to the ferromagnetic/antiferromagnetic exchange interaction between atoms on the martensitic transformation. In this sense, Passamani et al [64] reported that Ni 2-x Fe x Mn 1.44 Sn 0.56 alloys show a drastic shift of the martensitic transformation after the replacement of Fe atoms for Ni and/or Mn. In this case, Fe-Mn ferromagnetic interactions compensate Mn-Mn antiferromagnetic ones, which leads to the stabilization of austenite phase.…”
Section: Other Factors Affecting Transition Temperaturementioning
confidence: 99%
“…Further details about preparation and characterization of our samples can be found elsewhere [10]. ZFC and FC measurements of magnetization as a function of temperature M (T ) and magnetic field M (H) were performed using a Quantum Design-MPMS-5 SQUID magnetometer working in the temperature range from 2 to 400K and the field range from 0 to 50kOe [10]. $ %& the second order phase transitions.…”
Section: Samples Characterization and Magnetic Measurementsmentioning
confidence: 99%